Determinants of dividend payout decisions: A dynamic panel data analysis of Turkish stock market - Faruk Bostanci; Eyup Kadioglu; Guven Sayilgan (International Journal of Financial Studies, 2018)
This study analyzes the firm-specific factors affecting the dividend payout decisions of the companies whose shares are traded on the Borsa Istanbul stock exchange. To this end, the dynamic panel regression is applied to 853 observations of yearly average of 106 companies listed on the Borsa Istanbul between 2009 and 2015. According to results from the Arellano-Bover/Blunder-Bond two-step system generalized method of moments, a statistically significant positive effect on dividend payout was found in the relationship between the dividend payout of the previous year, the company's return on equity and the market value/book value ratio, liquidity and the company's size. The demonstration of a positive relationship between dividend payout and return on equity supports the free cash flow hypothesis and the positive relationship with the previous year's dividend payout ratio supports the dividend smoothing hypothesis for Turkey.
Keywords: G10; G30; G35; G38; 330; dividend; free cash flow hypothesis; dividend smoothing hypothesis; dividend irrelevance hypothesis; dynamic panel; Borsa Istanbul